(untitled) (Research, Society and Development, 2021)
Analyze the published scientific evidence about the contributions of nursing care to the prevention of falls and fractures in the health care of the elderly. The present study deals with a bibliographic review of the integrative literature review method, carried out between November 2020 and January 2021. The search was carried out, through the - VHL, using the LILACS, BDENF databases, and through from SCIELO. Adhering to the descriptors / keywords: “Nursing care”, “Elderly”, “Accidents due to falls”, combined with the Boolean operator “AND”. Nurses carry out care actions, through the knowledge of risk factors and the implementation of preventive actions for falls in the elderly and immediate care actions. The nursing professional, along with the multidisciplinary team, must have a holistic view of the elderly patient, so the nurse has to observe the theoretical and practical how to analyze the risk factors to have a scientific basis, such as, in Primary Health Care, designing care for each case from guidelines for a safe environment strategic plan, use of auxiliary devices, medications used, analyzing the risk and benefit among different needs. From the identification of the risk of falling by the nurse, he will be able to formulate an action plan and, later, evaluate the results of the assistance provided. In this context, falls in elderly patients cause physical and psychological trauma, loss of independence and even the risk of death. Thus, it is imperative that nursing professionals are aware of the risk factors for the occurrence of this event.